Comparative analysis of different surfaces for integrated solar heating and radiative cooling: A numerical study. (15th July 2018) - Hu, Mingke; Zhao, Bin; Ao, Xianze; Su, Yuehong; Wang, Yunyun; Pei, Gang
Abstract: The spectral selectivity of solar selective absorbing coatings enhances coating performance in diurnal heating collection but also limits the potential application of these materials in nocturnal radiative cooling. A radiative cooling surface shows poor solar heating performance due to the same reason. The present study proposed a novel surface that combines solar heating and radiative cooling (SH-RC) considering the spectral selectivity of photo-thermic conversion and radiative cooling. A hypothetical SH-RC surface was also proposed. This hypothetical surface had an absorptivity of 0.92 in the solar radiation band, emissivity of 0.70 in the "atmospheric window" band, and absorptivity (emissivity) of 0.05 in other bands. The thermal performance of this spectrally selective SH-RC surface (SH-RCs surface) was numerically investigated by comparing it with three surfaces, namely, solar selective absorbing coating surface (SH surface), spectrally selective radiative cooling surface (RC surface), and spectrally non-selective black surface (SH-RCblack surface). Results indicated that the SH-RCs surface is most suitable for achieving integrated SH and RC. In a typical summer day, the heat gains of the SH, RC, SH-RCblack, and SH-RCs surfaces are 17.14, 0, 15.57, and 13.22 MJ/m 2, respectively. The cooling energy gains of the four surfaces are 0, 1.02, 0.95, and 1.01 MJ/m 2, respectively. Highlights: A surface to realize combined solar heating and radiative cooling (SH-RC) functions. The ideal spectral selectivity of the SH-RC surface was introduced. A thermal model considering spectral radiant distribution was established. The performance of a SH-RC surface was studied and compared with other surfaces.